Site‐specific fab fragment biotinylation at the conserved nucleotide binding site for enhanced ebola detection. Issue 7 (30th April 2015) - Mustafaoglu, Nur; Alves, Nathan J.; Bilgicer, Basar
ABSTRACT The nucleotide binding site (NBS) is a highly conserved region between the variable light and heavy chains at the Fab domains of all antibodies, and a small molecule that we identified, indole‐3‐butyric acid (IBA), binds specifically to this site. Fab fragment, with its small size and simple production methods compared to intact antibody, is good candidate for use in miniaturized diagnostic devices and targeted therapeutic applications. However, commonly used modification techniques are not well suited for Fab fragments as they are often more delicate than intact antibodies. Fab fragments are of particular interest for sensor surface functionalization but immobilization results in damage to the antigen binding site and greatly reduced activity due to their truncated size that allows only a small area that can bind to surfaces without impeding antigen binding. In this study, we describe an NBS‐UV photocrosslinking functionalization method (UV‐NBSBiotin) in which a Fab fragment is site‐specifically biotinylated with an IBA‐EG11‐Biotin linker via UV energy exposure (1 J/cm2) without affecting its antigen binding activity. This study demonstrates successful immobilization of biotinylated Ebola detecting Fab fragment (KZ52 Fab fragment) via the UV‐NBSBiotin method yielding 1031‐fold and 2‐fold better antigen detection sensitivity compared to commonly used immobilization methods: direct physical adsorption and NHS‐Biotin functionalization, respectively. Utilization of the UV‐NBSBiotin method for site‐specific conjugation to Fab fragment represents a proof of concept use of Fab fragment for various diagnostic and therapeutic applications with numerous fluorescent probes, affinity molecules and peptides. Biotechnol. Bioeng. 2015;112: 1327–1334. © 2015 Wiley Periodicals, Inc.